Kalibrasi Sumbu Y Terhadap Ketelitian Benda Kerja Pada Mesin CNC Router 3 Axis - Putra, Fajar Wijaya, Bambang Waluyo F, ST. MT, Ir. Agus Hariyanto, MT (2016)
The purpose of this study is to determine how much influence the calibration process is done on the Y axis of the rigor of the workpiece on the machine 3 AXIS CNC ROUTER.In the research process conducted three funeral process variation before and after calibration process to form squares, circles and hexagons .it calibration used on CNC machines ROUTER 3 AXIS is using software MACH 3 mill.In this experiment the irregularities found irregularities that occurred on the outcome of the workpiece feeds .penyimpangan The size of the workpiece prior to the calibration process, namely the hexagonal side feeds the workpiece H is 0.1205 mm and the smallest at the funeral workpiece side circle E is 0,0182mm , And in the process of calibrating the largest funeral after funeral workpiece that is at hand hexagon L is 0.0709 and the smallest deviation that is on the workpiece side of circle F is 0,0152mm.